2022
DOI: 10.1186/s13063-022-06105-2
|View full text |Cite
|
Sign up to set email alerts
|

A multiple technology-based physical activity intervention for Latina adolescents in the USA: randomized controlled trial study protocol for Chicas Fuertes

Abstract: Background Latina adolescents in the USA report some of the lowest rates of physical activity of any demographic subgroup; this is paralleled by a markedly higher lifetime risk of obesity, type 2 diabetes, and other conditions related to inactivity. Despite this, to date, no fully powered clinical trials have tested physical activity interventions specifically for this population. High use of mobile technologies (including text messages, smartphone apps, and social media) suggests this could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…A search in the literature revealed that multicomponent interventions with mHealth components involved school staff in a variety of ways-e.g., teacher-led online educational modules, face-to-face counseling regarding behavior change strategies, regular visits to school nurses aiming at boosting students' motivation, web-based material for school staff to learn about how to promote students' decision-making, workshops, and suggestions for environmental changes. These programs with mHealth components targeted physical inactivity, 94 smoking, 95 or a combination of behaviors such as physical activity and diet [96][97][98][99] or alcohol, smoking, sleep, and screen time. 100 Text messages and health applications (apps) were used to deliver the mHealth component; sometimes combined with fitness trackers and social media peer-groups.…”
Section: The History Of Mhealthmentioning
confidence: 99%
See 2 more Smart Citations
“…A search in the literature revealed that multicomponent interventions with mHealth components involved school staff in a variety of ways-e.g., teacher-led online educational modules, face-to-face counseling regarding behavior change strategies, regular visits to school nurses aiming at boosting students' motivation, web-based material for school staff to learn about how to promote students' decision-making, workshops, and suggestions for environmental changes. These programs with mHealth components targeted physical inactivity, 94 smoking, 95 or a combination of behaviors such as physical activity and diet [96][97][98][99] or alcohol, smoking, sleep, and screen time. 100 Text messages and health applications (apps) were used to deliver the mHealth component; sometimes combined with fitness trackers and social media peer-groups.…”
Section: The History Of Mhealthmentioning
confidence: 99%
“…100 Text messages and health applications (apps) were used to deliver the mHealth component; sometimes combined with fitness trackers and social media peer-groups. 95,97,[99][100][101][102][103] In contrast, stand-alone mHealth interventions require minimal efforts from school staff and do not interfere with teacher-led activities. Numerous stand-alone mHealth interventions were identified in the literature.…”
Section: The History Of Mhealthmentioning
confidence: 99%
See 1 more Smart Citation